PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1938)
Abstract The article presents accounting problems which were prepared by the Board of Examiners of the American Institute of Accountants and used by the many cooperating States in the examinations held on May 12th and 13th, 2004. The examination in accounting theory and practice is divided into two parts and the first part of this examination is presented here. Acme Manufacturing Corp. uses a process-cost system; manufacturing costs, other than direct materials and direct labor, are applied to the product in an amount equal to 50% of the direct labor cost and, per contra, are credited to an account, "indirect costs absorbed." The books were closed as of December 31, 1937 when the inventory of goods in process in Process A consisted of 1,000 units of product. In January, 1938, 10,000 additional units of product were started; material requirements in full were issued at a cost of $31,000; direct labor amounted to $39,900; indirect cost was applied at 30 percent of the direct labor cost; 9,000 units were completed and transferred to the next process; 2,000 units remained in process on January 31st with material fully supplied and labor averaging 50 percent complete. The examinee is asked to set up a goods-in-process account for Process A showing total and unit material labor and indirect costs for units completed and for units in process at end.